MENINGKATKAN HASIL BELAJAR IPS TENTANG KEDUDUKAN DALAM KELUARGA DENGAN PENDEKATAN PAKEM - Windhiyanti Windhiyanti (Perspektif Ilmu Pendidikan, 2011)
The purpose of this study was to obtain empirical data on learning achievement in Social Sciences on the position in the family. The study was conducted in Grade 2 of State Primary School 01, Morning School, in Cilandak Timur. The study applied active, creative, effective, and joyfull learning (PAKEM) approach. The subjects were Grade 2 students in the second semesterof 2008/2009 school year. As an action research, the spiral model or S cycle introduced by Kemmis and Mc Taggard was used. The steps included planning, acting, observing, reflecting, and evaluating, as the bases for the following cycle. The result of the study showed there is a significant learning achievement improvement of the students at the end of the second cycle. The study indicates PAKEM approach can be applied as one of the solution of improving the students’ learning achievement in Social Sciences particularly in Grade 2 of Primary School.